Efeito da nutrição mineral in ovo sobre o desenvolvimento ósseo e desempenho em frangos de corte - Oliveira, Tiago Ferreira Birro (2016)
Effects of the in ovo injection of commercial diluent containing supplemental microminerals (Zn, Mn, and Cu) on hatchability, hatching chick quality variables and the in ovo injection of organic Zn, Mn and Cu in association with post-hatch (poh) holding time (HT; feed and water restriction) on percentage of bone ash (PBA) and the concentration of minerals in the tibia of broilersin Ross × Ross 708 broilers were examined. On 17 d of incubation (doi) eggs were subjected to 1 of 4 treatments using a commercial multi-egg injector. Treatments included non-injected(treatment 1) and diluent-injected (treatment 2) control groups. Those in treatment 3 received diluent containing 0.181, 0.087 and 0.010 mg/ml of Zn, Mn and Cu, respectively, and those in treatment 4 received diluent containing 0.544, 0.260 and 0.030 mg/ml of Zn, Mn and Cu, respectively. The4 TRT groups from the incubation phase were then sub-divided into 2poh HT groups. Fifteen birds were randomly allocated to each of 6 replicate mini pens in each of the 8 (4x2) TRT. The first HT group(0HT) had immediate access to water and feed, and the second HT group (24HT) contained birds that were kept in transport baskets for 24 h before being released.Hatchability of fertile eggs set (HF) was determined on 20.5 and 21.5 doi. On 21.5 doi,HF and mean hatching chick weight (MHW) were determined. The tibiae fresh and dry weight, length, width, bone breaking strength (BBS) and percentage of bone ash (PBA) were determined. There was a significant injection treatment effect on HF at 21.5 doi. The HF of eggs at 21.5 doi in treatment 4 was significantly lower than that of the non-injected control group, with treatment3 being intermediate. However, embryos from eggs that received treatment 4 had a significantly higher PBA in comparison to all other treatment. The in ovo injection of these organic minerals had a positive influence on bone mineralization.